Multiphysics Computational Modeling of Nuclear Reactors Small Size Through the Coupling of Serpent Codes and Fluent - Erik Lago; Dany Sanchez Dominguez; Leorlen Rojas Mazaíra (Brazilian Journal of Radiation Sciences)
The study of nuclear energy using computational codes has been widely explored by nuclear engineering researchers through various calculations over the years, with emphasis on neutron and thermo-hydraulic calculations. The need for designing a reactor model that would produce energy at a lower cost per MWh highlighted the importance of Small Modular Reactor (SMR) reactors. Development: The present work aims to carry out a study related to the coupling of two computational codes, SERPENT and ANSYS FLUENT, using an SMR PWR reactor model (Pressurized Water Reactor) from the company B&W Generation, called mPower. Methods: The geometry of a pin of the mPower reactor was modeled and neutronics analyses of the model were performed using SERPENT code, while thermo-hydraulic analysis was simulated using FLUENT code. A coupling algorithm between these two simulation tools was built to automate the process of obtaining operational conditions for the effective operation of the reactor. Results: This work enabled the development of a tool that performs the multiphysics coupling between neutronic and thermos-hydraulic phenomena on mPower fuel pin. Conclusion: Multiphysics simulation, which considers the interaction between neutronic and thermal dynamics, provides an enhanced understanding of reactor operation. In this simulation, the power distribution generated by the neutronic code is used as input for the thermo-hydraulic code. Conversely, the temperature distribution obtained from the thermo-hydraulic simulation is fed back into a subsequent iteration of the neutronic analysis, thus achieving a coupling between these phenomena.  To obtain accurate estimates for the power and temperature distributions, an automated process based on Python programming was implemented.